2019
DOI: 10.2140/agt.2019.19.1229
|View full text |Cite
|
Sign up to set email alerts
|

Uniform exponential growth for CAT(0) square complexes

Abstract: In this paper we start the inquiry into proving uniform exponential growth in the context of groups acting on CAT(0) cube complexes. We address free group actions on CAT(0) square complexes and prove a more general statement. This says that if F is a finite collection of hyperbolic automorphisms of a CAT(0) square complex X, then either there exists a pair of words of length at most 10 in F which freely generate a free semigroup, or all elements of F stabilize a flat (of dimension 1 or 2 in X). As a corollary,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 14 publications
2
24
0
Order By: Relevance
“…Remark 4.1. The case n = 2 of Theorem 1.2 can be deduced from the work of Kar and Sageev who study uniform exponential growth of groups acting freely on CAT(0) square complexes [KS16]. They prove that for any two elements x, y there exists a pair of words of length at most 10 in x, y that freely generates a free semigroup, unless x, y is virtually abelian.…”
Section: Proof Of Theorem 12mentioning
confidence: 99%
See 2 more Smart Citations
“…Remark 4.1. The case n = 2 of Theorem 1.2 can be deduced from the work of Kar and Sageev who study uniform exponential growth of groups acting freely on CAT(0) square complexes [KS16]. They prove that for any two elements x, y there exists a pair of words of length at most 10 in x, y that freely generates a free semigroup, unless x, y is virtually abelian.…”
Section: Proof Of Theorem 12mentioning
confidence: 99%
“…Pride's construction has been revisited in [JW17]. We observe that the case n = 2 can be deduced from the work of Kar and Sageev who study uniform exponential growth of groups acting freely on CAT(0) square complexes [KS16]. See Remark 4.1.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Kar and Sageev showed that if a group acts freely on a CAT(0) square complex, then either it has uniform exponential growth or it is virtually abelian [KS19] . In this article, we generalize the result of Kar and Sageev by removing the assumption of a free action.…”
Section: Introductionmentioning
confidence: 99%
“…Find a constant λ such that either G is virtually abelian or, for any finite generating set of G, the λ-ball in the corresponding Cayley graph of G contains two elements that freely generate a free (semi)group. There is quite a strong result about this in the 2-dimensional case, due to Kar and Sageev [KS19], and this is an actively-studied question in higher dimensions.…”
mentioning
confidence: 96%